Design of a stress-dependent deep-level transient spectroscopy instrument for the study of the structural properties of defects in semiconductors - Meyer, W.E. (Walter Ernst) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.